Vector construction to enhance GP5 antigen expression of virus PRRS in plant cells - Sen, Đào Thị; Mai, Nguyễn Chi; Liên, Lê Quỳnh; Linh, Trần Mỹ; Hà, Chu Hoàng; Vân, Nguyễn Tường (Vietnam Journal of Biotechnology, 2016)
Plant vaccine is a new tool to enrich available vaccine resources for protection of human and animal health. Plant vaccine offers several advantages over current conventional vaccines, including that storage and transportationare convenient after lyophilization, production costs are low, and the contamination of mammalian pathogens is avoided. However, the low expression of foreign genes in plant still exists that limits the application of this kind of vaccine. Presently, plant virus-based expression vectors represent a technology that enables high levels of recombination proteins to be produced efficiently in plant cells. In this study, a modified TMV-based vector to elevate glycoprotein GP5 of PRRSV in plant cells without negative effects in the development of plant cells was developed. Gene encoded GP5 was replaced CP of TMV and the whole was regulated by the heat shock protein Hsp 18.2 promoter. Transgenic BY-2 cells carrying pHsp-TMV-GP5 showed the normal development compared to the ones harbouring pCB-35S-TMV-GP5. The results showed that the Hsp-TMV-GP5 construct do not have a negative effect on viability of transgenic plant cells. A further study will be carried out to investigate the expression of GP5 in stable transgenic plant cells to confirm the benefit of the modified expression vector in development of rapid and cost-effective antigens in plant cell suspension culture.